KORELASI KADAR KREATININ SERUM DENGAN HASIL TES ALBUMIN URINE PADA PASIEN DENGAN PENYAKIT GINJAL DI RSUD dr. SOEGIRI LAMONGAN - ., Intashofal; ., Sukarjati (Jurnal Ilmu Kesehatan dan Kesehatan, 2017)
Abstract: Examination of blood creatinine levels is one of the parameters used to assess renalfunction, since serum and urinary excretion concentrations within 24 hours are relatively constant.However, in another clinical guideline, there is a type of examination that is more recommended inmost patients with the risk of kidney failure, urine albumin test. In the event of renal dysfunction,the ability of creatinine filtration will decrease and serum creatinine will increase as well as somesubstances that should not exist in the urine, such as albumin, to appear. Reduced albumin excretion in the urine may be able to slow the rate of renal failure and help to delay the body’s need forkidney or dialysis transplantation. This cross-sectional study aims to analyze the relationship between serum creatinine and albuminuria in patients with kidney disease. Serum creatinine levelexamination by Jaffe method and urine albumin examination were qualitatively performed on therespondents who met the inclusion criteria. A total of 92 data were then analyzed by Chi-squarewith α<0,05. The results of this study indicate that there is a significant relationship betweenserum creatinine and albuminuria levels in patients with general kidney disease (p = 0.000, r =0.728), and in male patients (p = 0.000, r = 0.736) and females (p = 0,000; r = 0.686) with theage level 41-50 years. There is no relationship between serum creatinine and albuminuria in maleand female patients at the age of 20-30 years and 31–40 years.